TANGGUNGJAWAB SOSIAL, STRATEGI DIVERSIFIKASI USAHA, DAN KINERJA PERUSAHAAN - Kusmawati . (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2012)
Theoretical consideration are used in this research to prove effect of corporate social responsibility between diversification strategies and performance of firm. This studi have benefit for managements of firm, investors, and researchers. Population in this research are the public manufacture companies that listed in the Indonesian stock Exchange (IDX). Sample are selected with purposive sampling method. Documentation method are used to collect data and moderating linier regretion are used to analysis data. This study show that corporate social responsibility can not be moderating variable in effect of diversivication strategies to performance of firm. Keyword: corporate social responsibility; diversification strategies; performance.